Preventing Childhood Obesity and Its Long-term Effects - Abigail L Shuman (Undergraduate Research Journal for the Human Sciences, 2024)
Childhood obesity affects nearly one in every five children and adolescents in the U.S. This epidemic has led to the development of chronic illnesses in adulthood, such as metabolic disorders, cardiovascular disease, sleep apnea, osteoarthritis, and asthma. This literature review examined intervention programs and their effectiveness in reducing childhood obesity. The application of health behavior theories and their impact on altering children's behavior was also explored. This paper presents an analysis that describes the success of multiple childhood obesity intervention programs in addition to effective prevention strategies. The findings associated the effectiveness of programs with the socioeconomic status of children, and suggested more substantial state or regional policies to increase physical activity in schools. The most successful childhood obesity intervention programs were implemented using close relationships, community resources, and a holistic approach.
Keywords: Childhood obesity; health behaviors; program effectiveness